If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5 + 9x = -19 + x Solving 5 + 9x = -19 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 5 + 9x + -1x = -19 + x + -1x Combine like terms: 9x + -1x = 8x 5 + 8x = -19 + x + -1x Combine like terms: x + -1x = 0 5 + 8x = -19 + 0 5 + 8x = -19 Add '-5' to each side of the equation. 5 + -5 + 8x = -19 + -5 Combine like terms: 5 + -5 = 0 0 + 8x = -19 + -5 8x = -19 + -5 Combine like terms: -19 + -5 = -24 8x = -24 Divide each side by '8'. x = -3 Simplifying x = -3
| 4a+5=10 | | 8(q+4)= | | 1.1(a+3)-5(3-0.2a)= | | (5x+1)3=0 | | -5-x=-125 | | 2x+14=-14-5x | | (2x-6)(x+7)=0 | | 4x+y=125 | | u^3-3u=0 | | (-10u+5)-(-2u-8)= | | x-8+4=21 | | 3v^2=5v+2 | | z^4-3(1+2i)-8-6i=0 | | a=180-360/n | | 3x^5-243x=0 | | 7x+1=44 | | 28x^2+41x+15=0 | | 2X+15=3X+5 | | 5(-2x-20)=140 | | 5x+8=17+2x | | xsquare+3=4y | | (2x+8)2=36 | | 3(2z-5)=4z+11 | | cos(x^2)=2 | | 7(a-3)+5(a+2)=37 | | 3x-3=6x-12 | | 5x^3+4x^2+3x+1=0 | | 1x^2-7x-10=0 | | y-17=x^2-8x | | 5x^3+3x^2-2x-2=0 | | 36x^2+24=0 | | 16/5y-4 |